The PI3K Inhibitor XH30 Enhances Response to Temozolomide in Drug-Resistant Glioblastoma via the Noncanonical Hedgehog Signaling Pathway - Ji, Ming; Zhang, Zhihui; Lin, Songwen; Wang, Chunyang; Jin, Jing; Xue, Nina; Xu, Heng; Chen, Xiaoguang (Frontiers in Pharmacology, 2021)
Glioblastoma multiforme (GBM) is the most common malignant tumor of the central nervous system. Temozolomide (TMZ)–based adjuvant treatment has improved overall survival, but clinical outcomes remain poor; TMZ resistance is one of the main reasons for this. Here, we report a new phosphatidylinositide 3-kinase inhibitor, XH30; this study aimed to assess the antitumor activity of this compound against TMZ-resistant GBM. XH30 inhibited cell proliferation in TMZ-resistant GBM cells (U251/TMZ and T98G) and induced cell cycle arrest in the G1 phase. In an orthotopic mouse model, XH30 suppressed TMZ-resistant tumor growth. XH30 was also shown to enhance TMZ cytotoxicity both in vitro and in vivo. Mechanistically, the synergistic effect of XH30 may be attributed to its repression of the key transcription factor GLI1 via the noncanonical hedgehog signaling pathway. XH30 reversed sonic hedgehog–triggered GLI1 activation and decreased GLI1 activation by insulin-like growth factor 1 via the noncanonical hedgehog signaling pathway. These results indicate that XH30 may represent a novel therapeutic option for TMZ-resistant GBM.